In vitro digestibility of diets with different levels of inclusion of moringa (Moring olifera) for growing lambs - Quintanilla-Medina, Jairo Jeú (2020)
The study aimed to evaluate different levels of inclusion of Moringa oleifera L. forage in diets for growing lambs on the kinetics of ruminal fermentation and in vitro degradability. Five treatments were used, expressed in g kg-1 DM and consisted of control (IM0 = 0), low inclusion level (IM10 = 100), medium inclusion levels (IM20 = 200 and IM30 = 300) and high inclusion level (IM40 = 400). No effect of moringa inclusion levels was observed at 6, 12 and 24 h; however, at 48 h the IM40 inclusion level obtained the lowest value (116.0 ml g-1). In the accumulated gas production at 48 and 72 h, a linear pattern was observed, as the level of inclusion of M. oleifera in the diet increases, gas production decreases. Likewise, it was observed that the in vitro digestibility of dry matter was affected by the level of inclusion of M. oleifera, observing a decrease in degradability as the level of inclusion increases, where the levels of 100 and 200 g kg-1 MS equalled the value observed for the control diet (796.3, 794.5 and 810.5 g kg-1 of DM, respectively). Using Moringa oleifera L. at levels less than 20% in diets for growing lambs represents a feeding alternative for production units.